Flexible mechanisms for reducing climate change in the 1997 Kyoto Protocol - Boutera, Chemama (Journal of Human Sciences, 2023)
The 1997 Kyoto Protocol to the United Nations Framework Convention on Climate Change is the international community’s first serious attempt to reduce greenhouse gas emissions. Contrary to the Framework Convention, the Protocol attempted to provide for specific obligations and commitments and set out two types of obligations: those of all States, and those of developed States, based on the principle of common but differentiated responsibilities. In order to be able to fulfil its obligations under the Protocol, States, in particular developed countries, have adopted market-based economic mechanisms that allow joint action by States to reduce greenhouse gas emissions, which are complementary to measures taken at the domestic level by States to protect the environment from the effects of climate change, and have been called "flexible mechanisms". This study illustrates the meaning and purpose of these mechanisms, their types and States’ position on their adoption of the Kyoto Protocol.